Re-Conceptualizing Developmental Areas of Assessment for Screening, Eligibility Determination and Program Planning in Early Intervention - Keilty, Bonnie; Blasco, Patricia M.; Acar, Serra (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Contemporary recommended practices in early childhood assessment strive to gain a holistic picture of child learning and development to inform screening, eligibility, and program planning decisions. These practices have traditionally focused on competencies reflected in developmental domains with limited attention to the approaches-to-learning used to acquire those competencies. In this article, we call for the examination of early childhood constructs that impact a child’s ability to learn and develop, such as executive function (EF), mastery motivation, self-regulation and self-determination, specifically in the infant-toddler period. With EF defined as a wide range of central control processes in the brain that link and categorize information that is discernible in cognitive, motor, and behavioral responses [1], we propose a model of EF as the core construct that drives and unites these learning processes and describe how the model can be applied to Part C early intervention screening, assessment, eligibility determination, and program planning, as well as identify future directions in research and personnel preparation.